Empowerment of Health Cadres to Prevent Child Marriage - Antarsih, Novita Rina; Ichwan, Erika Yulita; Aticeh (Jurnal Abdimas Peradaban, 2022)
Indonesia is the country with the highest child marriage after Cambodia. In addition, West Java Province has the highest absolute number of child marriages in Indonesia (273,300 child marriages). In addition, it also ranks first nationally for out-of-school children at the elementary, junior high, and high school/vocational school levels. Health cadres do not understand their duties and roles in reducing MMR, one of which is knowledge about the impact of child marriage. This activity aims to increase the knowledge and attitudes of health cadres through health education and to empower the potential of existing communities to prevent child marriage. This activity with Preparing, Participatory Programming, Reinventing Assets, Designing, Communicating, Implementing, and Evaluating. Results: The number of cadres who participated in counseling was 25 people. The potential that exists is the presence of midwives and community leaders. Youth of as many as 450 people, 20 children who dropped out of school had elementary school education, 18 had junior high school diplomas, and 4 cases of early marriage. Based on the SWOT analysis, Pondok Rajeg Kelurahan is in quadrant II which requires strategic diversification. Evaluation of activities revealed from the results of the Willcoxon test that there was an effect of health education using early marriage flyers on knowledge p-value = 0.002 (p-value < 0.05) and attitude p-value = 0.002 (p-value < 0.05). Health cadres understand one of their roles and duties from the influence of leaflets on increasing knowledge and positive changes in cadre attitudes to address the problem of early marriage. In addition, their commitment to implementing early marriage prevention and its impact.